Successful treatment of liver metastases arising from early gastric cancer achieved clinical complete response by nivolumab - Tsutomu Namikawa (Surgical Case Reports, 2018)
Abstract Background Although a recent randomized clinical trial has demonstrated that the objective response rate to nivolumab for metastatic gastric cancer was 11.2%, there was no patients confirmed complete response. Herein, we report on a case of liver metastasis arising from early gastric cancer in which a complete clinical response was achieved to nivolumab as third-line therapy. Case presentation A 77-year-old man was referred to Kochi Medical School Hospital for the treatment of liver metastases from gastric cancer. The patient had undergone laparoscopic total gastrectomy with regional lymph node dissection 30 months prior for early gastric cancer, with a final diagnosis of T1N0M0, stage IA. The patient developed solitary splenic metastasis measuring 42 mm 28 months later and underwent splenectomy because there was no evidence of further metastatic lesions in any other organ. The patient was treated with S-1 plus oxaliplatin based on negative immunohistochemical staining of the resected specimens for human epidermal growth factor receptor 2 (HER2). Four months after the splenectomy, the patient developed multiple liver metastases and was treated with ramucirumab plus paclitaxel. Because of disease progression, the patient was administered 3 mg/kg, i.v., nivolumab every 2 weeks. After 4 cycles of systemic treatment using nivolumab, abdominal computed tomography revealed marked shrinkage of the liver metastases. After 12 cycles of nivolumab, the liver metastases had disappeared completely. The patient did not develop any adverse reactions, including immune-reactive adverse events, during treatment. The patient continues to receive nivolumab, and there is no evidence of disease recurrence in the 8-month period since starting nivolumab. Conclusions To the best of our knowledge, this is the first case report in the English literature of a gastric cancer patient achieving a complete clinical response to nivolumab, and highlights the potential for successful treatment of metastatic gastric cancer using nivolumab.